2022
DOI: 10.1039/d1me00192b
|View full text |Cite
|
Sign up to set email alerts
|

Probing the evolution of conductivity and structural changes in vapor-F4TCNQ doped P3HT

Abstract: This study highlights the importance of granular understanding of conductivity and structural changes in vapor doped semiconducting polymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…The electrical conductivity of a doped polymer is determined by both the density and mobility of charge carriers, so it is important to understand how doping influences these two quantities. ,, Strong Coulombic binding between polarons and counterions can result in localized or trapped carriers that do not significantly contribute to the conductivity; in other words, there can be instances where a dopant oxidizes the polymer chain, but the resulting carriers do not contribute to the electrical conductivity because of their very low mobility. In crystalline polymer regions, dopant molecules usually reside among the alkyl side chains, away from the polymer backbone. , This positioning is generally desirable, as it reduces the Coulombic binding between polarons and their counterions . In disordered polymer regions, large void spaces between chains allow counterions to remain near polarons, which is partly responsible for the low conductivities observed in doped amorphous semiconducting polymers .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrical conductivity of a doped polymer is determined by both the density and mobility of charge carriers, so it is important to understand how doping influences these two quantities. ,, Strong Coulombic binding between polarons and counterions can result in localized or trapped carriers that do not significantly contribute to the conductivity; in other words, there can be instances where a dopant oxidizes the polymer chain, but the resulting carriers do not contribute to the electrical conductivity because of their very low mobility. In crystalline polymer regions, dopant molecules usually reside among the alkyl side chains, away from the polymer backbone. , This positioning is generally desirable, as it reduces the Coulombic binding between polarons and their counterions . In disordered polymer regions, large void spaces between chains allow counterions to remain near polarons, which is partly responsible for the low conductivities observed in doped amorphous semiconducting polymers .…”
Section: Introductionmentioning
confidence: 99%
“… 23 25 In crystalline polymer regions, dopant molecules usually reside among the alkyl side chains, away from the polymer backbone. 19 , 26 28 This positioning is generally desirable, as it reduces the Coulombic binding between polarons and their counterions. 17 In disordered polymer regions, large void spaces between chains allow counterions to remain near polarons, which is partly responsible for the low conductivities observed in doped amorphous semiconducting polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature, equilibrium between the neutral and ionized dopant, the size and shape of the dopant, the degree of solvent swelling, and doping reaction mechanism are all likely to affect how dopants diffuse into the film. 7,10,[12][13][14][15] The most extensive models of dopant diffusion have examined the diffusion coefficients of both the neutral and ionized form of two common dopants (F 4 TCNQ and Mo(tfd-CO 2 Me) 3 ), both of which oxidize the conjugated polymer by a charge transfer mechanism. 6,12,16 A study of diffusion of Mo(tfd-CO 2 Me) 3 into poly(3-hexylthiophene) (P3HT) thin films found that the surface concentration of Mo(tfd-CO 2 Me) 3 À saturates quickly and is essentially immobilized by coupling with the charged P3HT + .…”
Section: Introductionmentioning
confidence: 99%
“…A common doping method involves either immersion of semiconducting polymer films in solutions of the dopant (immersion doping) or thermal evaporation/sublimation of the dopant into the polymer film (vapor doping). Both methods have been used as platforms to control and investigate the mass transport of various dopants, including 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane (F 4 TCNQ), 6–10 molybdenum tris(1-(methoxycarbonyl)-2-(trifluoromethyl)ethane-1,2-dithiolene) (Mo(tfd-CO 2 Me) 3 ), 11,12 and phosphomolybdic acid (PMA). 13 Within these studies, diffusion has been quantified in the context of: (1) diffusion of the dopant as it is introduced into the film and (2) diffusion of the dopant in the solid state following the doping process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation